KEPEMIMPINAN PARTISIPATIF DALAM MEMBANGUN BUDAYA SEKOLAH YANG EFEKTIF DI SEKOLAH DASAR - Saripudin, Yusep; Yoseptry, Ricky; Iriantara, Yosal; Kartini, Tini; Anisusulawati, Anisusulawati; Nurjanah, Ana (PENDIDIKAN SAINS DAN TEKNOLOGI, 2025)
The results of the preliminary study show that SDN Sukawangi 2, as a basic education institution, is faced with challenges in building an effective organizational culture. Various factors such as management, communication between staff, involvement of teachers and staff in the decision-making process, and interaction with students still lack the implementation of leadership that is able to empower all school members to achieve common goals. This research aims to explore how participative leadership can build an effective school culture at SDN Sukawangi 2. This research uses qualitative methods using ethnographic techniques, case studies, document studies, observation or observations. Based on the results of research conducted through observations, interviews and documentation studies, it can be concluded that the participative leadership implemented by the school principal has succeeded in creating a school environment that is collaborative, inclusive and supports an effective learning process. Active participation from the entire school community, open communication, solid collaboration, involvement in every aspect of school management, and participatory decision making.